Reading Augustine in the Reformation: the flexibility of intellectual authority in Europe, 1500 - 1620 - Visser, Arnoud S. Q. (Oxford studies in historical theology, 2011)
The arrival of the printing press -- Humanist scholarship and editorial guidance -- Augustine after Trent -- How to find the right argument : bibliographies and indexes -- Customizing authority : anthologies and epitomes -- How readers read their Augustines -- Patristics and public debate